CORRECTION OF METABOLIC SYNDROME IN WOMEN IN PERIMENOPAUSE - M.S. RUSTAMOVA; M.KH. BADALOVA; S.M. MUKHAMADIEVA; S.S. NEGMATOVA; S.A. RADJABOVA (Avicenna Tajik State Medical University, 2018)
Objective: Study of the peculiarities of correction of metabolic disorders in women of the perimenopausal period Methods: 77 women were surveyed in perimenopause with metabolic syndrome (MS). Conducted analysis of hereditary prevalence and reproductive function; used clinical trails, studied carbohydrate and lipid metabolism, hormonal status; anthropometry, monitoring of arterial pressure, ultrasound of pelvic organs and liver. Results: Heredity in patients was burdened with cardiovascular diseases (58.4%), obesity (46.8%), diabetes mellitus (38.9%) and oncological pathology (18.2%). All interviewees have not given due attention to eating and enjoyed of food rich in carbohydrates in easily digestible form (81.8%). Patients showed: an increase in the body mass index (BMI) with an average value of 32±2.3 kg/m2, abdominal obesity (100%), insulin resistance (96.1%), dyslipidemia (84.4%), endocrinopathy (58.4%), hyperglycemia (55.8%), arterial hypertension (50.6%), androgen-dependent manifestations (32.5%), "Negroid acanthosis" (31,2%), steatosis of the liver (41.6%). Correction MS included a rational diet, increased motor activity, the appointment Metfogamma and Inoclim. The re-examination showed stabilization of the weight, reliable HOMA index reduction, general cholesterol content, low-density lipoprotein, and an increase of high-density lipoprotein level (p<0.05). Vegetovascular manifestations eliminated in 54.5% of women. Conclusion: Timely diagnosis and correction of metabolic disorders in women of perimenopausal age normalizes the main metabolism, eliminates the manifestations of menopause syndrome and positively affects the quality of their lives.